TRANSFORMATION OF OK OCE MSMES THROUGH DIGITAL CONTENT STRATEGY TO INCREASE BRAND AWARENESS AND COMPETITIVENESS - Andyan Pradipta Utama; Loeky Rono Pradopo; Yudo Devianto; Iwan Firdaus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid development of digital marketing has intensified business competition and encouraged the emergence of new entrepreneurs, requiring micro, small, and medium enterprises (MSMEs) to strengthen their competitiveness through effective branding strategies. Consumers increasingly prefer well-known brands because they are perceived as more trustworthy, accessible, and capable of delivering consistent quality. Therefore, digital content marketing has become an important instrument for enhancing brand awareness and supporting business sustainability. However, preliminary observations indicated that MSMEs affiliated with OK OCE in Jakarta had not optimally implemented digital content strategies to strengthen their brand identity and market visibility. In collaboration with Universiti Malaysia Terengganu (UMT), this community service program aimed to improve the capacity of MSME entrepreneurs in developing digital content marketing strategies to increase brand awareness and business competitiveness. The activity involved 33 OK OCE MSME members and was conducted through face-to-face workshops, discussions, practical content creation sessions, and mentoring activities. The training materials covered brand awareness concepts, content planning, social media utilization, and the use of simple digital tools such as Canva and CapCut. The evaluation results demonstrated that 88% of participants experienced an increased understanding of digital content marketing and brand awareness, while 70% successfully created or optimized their business social media profiles during the program. Participants also expressed their commitment to implementing structured content plans to support future business development. These findings indicate that community-based digital marketing education effectively enhances MSME capabilities and contributes to sustainable business growth in increasingly competitive digital markets.